In-store promotional campaign: The impact of a new fragrance - Rosa, Catarina Conde (2014)
The luxury market has evolved throughout time and even today, with the current news about the economic downturn, it is surprising to realize that this market continues to grow. The success lies not only on the constant affluence of customers with willingness to purchase luxury, but mainly depends on the continuous work held by luxury brands either by creating innovating and creative products, either by strengthening their relationship with the consumer. Moreover, this thesis aims to study the impact of an in-store promotional campaign within the launch of the new feminine fragrance of Balenciaga, named Florabotânica on the consumer’s awareness and willingness to experiment and, furthermore, to understand the Portuguese consumer behavior towards a selective fragrance store named Perfumes & Companhia. The analysis relies on the results obtained by a survey held in four different stores of the group. Findings point out the inexistence of awareness of the promotional campaign set by the brand, which calls into question the efficiency of this marketing strategy in the fragrance market. Still, it was taken into consideration the internal and external factors that may have influenced the final results such as the product characteristics, action from competitors and the consumer behavior towards a fragrance store. Regarding the consumer’s profile of Perfumes & Companhia stores, findings show that the consumer does a planned consumption process and does not spend much time in front of the linear. In addition, in the study, it was concluded that, sampling and beauty assistants are perceived as important drivers on the purchase process by the consumers. Luxury brands success lies on innovation and creativity, thus it is critical to always search new and better marketing strategies in-store that will be able to attract the consumer and make him fall for that luxury product.